Synchronous microwave ablation followed by core‐needle biopsy via a coaxial cannula for highly suspected malignant lung ground‐glass opacities: A single‐center, single‐arm retrospective study - FanLei Kong (Wiley, 2021)
Abstract Background This study aimed to retrospectively explore the safety and feasibility of computed tomography (CT)‐guided synchronous microwave ablation (MWA) followed by core‐needle biopsy (CNB) via a coaxial cannula for highly suspected malignant lung ground‐glass opacities (GGOs). Methods The clinical data of 66 patients (66 GGOs) treated with CT‐guided synchronous MWA followed by CNB via a coaxial cannula from January 2019 to January 2021 were included in this study. The technical success rate, curative effect, and complications were evaluated. Results Technical success rates were 100%. The pneumothorax rate was 36.4% (24/66). 72.7% (48/66) patients had the bronchopulmonary hemorrhage, 81.3% of hemorrhage was attributable to CNB. 24.2% (16/66) patients had varying degrees of pleural effusion. The pathological results were adenocarcinomas (n = 44), atypical adenomatous hyperplasia (n = 2), chronic inflammation (n = 3) and indeterminate pathological diagnosis (n = 17) with a 69.7% (46/66) positive diagnosis rate. The therapeutic response rate was 100.0% (66/66). Conclusions Synchronous MWA followed by CNB via a coaxial cannula has a satisfactory ablation effectiveness and an acceptable biopsy positive rate, which is an alternative treatment for highly suspected malignant GGOs.